Business Strategy Development of PT Anugrah Alam Mitra Makmur - Martina; Rizal Syarief; Asep Taryana (School of Business, IPB University (SB-IPB), 2024)
Background: PT Anugrah Alam Mitra Makmur (PT AA) is a logistics company specializing in Group C mineral resources. Internal and external conditions present opportunities for PT AA to expand its business.Purpose: The research objectives are (1) to analyze internal and external factors affecting the company and (2) to formulate strategies to develop the company. Design/methodology/approach: Data types included primary and secondary sources, with methods like Valuable, Rare, Inimitable, Organized (VRIO) for evaluating competitive advantages, PESTEL for understanding external factors, and Strength, Weakness, Opportunity, Threat (SWOT) for strategy formulation.Findings/results: The study revealed that most of PT AA's internal competencies and resources resulted in competitive parity, indicating a lack of significant advantages in its business operations. The PESTEL analysis identified external factors such as economic growth, increased construction industry activities, company-community relations, technological advancements, information accessibility, local environmental conditions, legal factors, and environmental issues. Based on these internal and external conditions, strategies were formulated using SWOT analysis, including Strength-Opportunity (SO), Strength-Threat (ST), Weakness-Opportunity (WO), and Weakness-Threat (WT) strategies.Conclusion: The resulting strategies involve expanding the target market, enhancing customer loyalty, increasing company capacity, improving the dissemination of information about the company, creating a forecast plan for purchases, types of materials, and transportation usage, conducting and deepening regular inspections, and conducting periodic evaluations. Keywords: mineral C, formulate strategies, logistics company, SWOT, VRIO